EPISTEMOLOGI FALSIFIKASI; IMPLIKASI PEMIKIRAN KARL RAIMUND POPPER TERHADAP KAJIAN KEILMUAN ISLAM - Ari Yuwono, Adhimas Alifian Yuwono (Program Studi Ilmu Tasawuf IAI Pangeran Diponegoro Nganjuk, Jawa Timur, 2024)
AbstractIslam as Science is a perspective that perpetuates scientific discourse that continues to move and develop and is open to other concepts in order to achieve scientific progress in Islam. One of the concepts in the epistemology area is Karl Raimund Popper's falsification. This research aims to review the concept of falsification and its implications for Islamic science. The method used in this research is a literature study by collecting books, journals, and websites related to the research theme to conduct a critical review, through the heuristic approach and inherent coherence. The result of this research is that Popper's falsification is a form of testing the theory that has been valid and established, by looking at the potential for being wrong or irrelevant on the one hand, and strengthening the theory if it is still proven to be correct and relevant on the other. The implication of Popper's falsification in Islamic scientific studies is to eliminate the dogmatism of religious groups that claim the truth of an understanding while blaming different understandings from other groups. In addition, through Popper's three-world concept, Islamic scientific studies can enter a dynamic space with a good sense of inclusiveness.